Incidence of neonatal macrocephaly at the Hospital Cayetano Heredia, 2016 - 2017. - Munayco Cortez, Carol (2019)
Objective: To determine the incidence of neonatal macrocephaly in a third level hospital from Lima, Peru. Methods: Macrocephaly was defined on the basis of a cephalic perimeter higher than the 97th percentile for age and sex. The report records of the Perinatal Computer System of Cayetano Heredia Hospital between January 1st., 2016 and December 31st, 2017 were used, as well as the Fenton growth chart to determine the limits of normality. Results: A total of 210 cases of neonatal macrocephaly was registered, a general rate of 26 per 1,000 live births. Neonatal macrocephaly incidence were inversely proportional to gestational age. Conclusions: Macrocephaly was higher in preterm neonates, with a risk factor five times higher in this population group.